Implementation of Determination of Families Recipients of Direct Cash Assistance Through Village Funds (DCA-VF) in Nagrak Village, Sukabumi Regency in 2022 - M Rijal Amirulloh; Fanisya Dewi Rahmalia; Risma Sri Mulyani Sundari (Department of State Administration - Musamus University, 2023)
This study aims to determine the implementation of the Direct Cash Assistance program implementation starting from the socialization of RT/RW and Musdesus to the implementation of the program. This study uses qualitative methods and determines the informants used to obtain information for the correctness of the data and validation of the data. Collecting data using the method of observation, interviews, and documentation. Data analysis techniques use the theory of Miles and Huberman. This study uses the implementation theory approach of the George Edwards III model. The success of this theory is measured by communication, resources, disposition, and bureaucratic structure. The results of the study showed that several obstacles occurred in the program, namely (1) several beneficiary families did not meet the program's criteria. (2) there are some invalid KPM data. In this case, the village government as the executor of the DCA-VF Program is looking for solutions and alternatives to overcome these problems so that the Village Fund Direct Cash Assistance Program can be implemented in Nagrak Village, namely, the Village government is more thorough in recording KPM criteria. It is necessary to re-emphasize socialization to the local RT/RW regarding the direct village fund cash assistance program (DCA-VF) as an effort to minimize social jealousy among the people of Nagrak Village, Cisaat District, Sukabumi Regency.